Nâng cao hoạt tính xúc tác của perovskit La0,4Sr0,6CoO3 đối với phản ứng DeNOx bằng cách pha tạp ion bạc - Nguyệt, Trần Thị Minh; Huấn, Nguyễn Quang; Thư, Hà Phương; Thai, Nguyễn Doãn; Trung, Nguyễn Quốc; Chi, Trần Quế; Chân, Đỗ Thế; Quí, Trần Văn (Vietnam Journal of Chemistry, 2012)
Mixed oxides of La, Sr, Co and Ag were prepared by sol-gel method using acid citrat as solvent. Two kinds of obtained mixed oxides A = La1-xSrxCoO3+La2O3+SrO+Co3O4+ SrCoOx and B = A+Ag were characterizied by X-Ray Diffraction analysis (XRD), Field Emision Scanning Electron Microscope (FESEM), Energy Dispersive X-ray Spectroscopy (EDS). Their catalytic activity was studied by Temperature Programmed Surface Reaction (TPSR). The results shown that the mixed oxide A exhibits a weak DeNOx activity, but in the addition of a little of metal silver (Ag), the NOx conversion increases remakably from 29.4% (in absence Ag) to 82.4% at 220oC.